(untitled) (Música Hodie, 2023)
The purpose of this study is to reveal a general picture of the phenomenon that concert performance represents and how its content and functioning are directly influenced by its practical and theoretical components. The materials for studying the main theme include information that reveals the evolution of the concert and performance art, its continuous modernisation and broadening of its scope. The methods used to study the above-mentioned object are system analysis, the principle of deriving categories and generalising the data obtained by creating a panoramic picture reflecting the volume and multi-component nature of the phenomenon under study as a holistic system. The result of the work performed is, on the one hand, to establish a set of the most important categories – the elements of theoretical and practical components of concert and performance activity and, on the other hand, to form a picture-panorama which gives a general idea of the issue, its content and the ways of its implementation in the life of society. The opinions of scholars from different countries, schools, stylistic and research fields concerning the topic of the title are also presented.